2009
DOI: 10.1073/pnas.0812879106
|View full text |Cite
|
Sign up to set email alerts
|

The type III TGF-β receptor regulates epithelial and cancer cell migration through β-arrestin2-mediated activation of Cdc42

Abstract: Loss of expression of the TGF-␤ superfamily coreceptor, the type III TGF-␤ receptor (T␤RIII or betaglycan), occurs in a broad spectrum of human cancers including breast, lung, ovarian, pancreatic, prostate, and renal cell cancer. T␤RIII suppresses cancer progression in vivo, at least in part, by reducing cancer cell motility. However, the mechanism by which T␤RIII regulates migration is unknown. Here, we demonstrate an unexpected TGF-␤ signaling independent role for T␤RIII in activating Cdc42, altering the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
141
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(145 citation statements)
references
References 38 publications
(74 reference statements)
4
141
0
Order By: Relevance
“…During coronary vessel development, TGFβR3 is dynamically regulated and is required; TGFβR3‐null mice cannot survive after embryonic day 14.5 21. In addition, β‐arrestin2 promotes the endocytosis of TGFβR3, and TGFβR3 and β‐arrestin2 coordinately function to regulate epithelial and cancer cell migration 22. Interestingly, TGFβR3 expression is significantly suppressed in rat lungs during long‐term anoxia (day 14) 23.…”
Section: Discussionmentioning
confidence: 99%
“…During coronary vessel development, TGFβR3 is dynamically regulated and is required; TGFβR3‐null mice cannot survive after embryonic day 14.5 21. In addition, β‐arrestin2 promotes the endocytosis of TGFβR3, and TGFβR3 and β‐arrestin2 coordinately function to regulate epithelial and cancer cell migration 22. Interestingly, TGFβR3 expression is significantly suppressed in rat lungs during long‐term anoxia (day 14) 23.…”
Section: Discussionmentioning
confidence: 99%
“…First, endoglin shares sequence similarity with the other TGF-b co-receptor betaglycan (also known as TGF-b receptor III). Betaglycan can also inhibit cell migration independently of TGF-b and its receptors, and instead associates directly with b-arrestin (Mythreye and Blobe, 2009). Here we observed that endoglin expression modulates focal adhesion formation and turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of TBR3 expression has been reported in multiple cancers, with loss of expression correlating with progression and worse prognosis (Dong et al 2007;Gatza et al 2010;Mythreye and Blobe 2009;Hanks et al 2013;Gordon et al 2008). In breast cancer, TBR3 inhibits cell migration and invasion, supporting a tumor suppressor function (Dong et al 2007).…”
Section: Introductionmentioning
confidence: 99%